2021
DOI: 10.1021/acs.molpharmaceut.1c00514
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal Administration of a Cisplatin-Loaded Nanogel through a Hybrid System Containing an Alginic Acid-Based Nanogel and an In Situ Cross-Linkable Hydrogel for Peritoneal Dissemination of Ovarian Cancer

Abstract: Intraperitoneal chemotherapy demonstrates potential applicability in the treatment of peritoneally disseminated ovarian cancer because the disseminated tumors can directly receive exposure to high concentrations of anticancer drugs. However, a considerable proportion of drugs, particularly micromolecular and hydrophilic drugs, such as cisplatin (CDDP), are often excreted through glomerular filtration for a short period. To effectively deliver CDDP into peritoneally disseminated ovarian cancer tissues, we devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Moreover, it has the specific ability to form hydrogels with a high water content that makes them similar to native soft tissue. The alginate-based hybrid system of cisplatin-loaded alginate nanogel encapsulated in an injectable alginate hydrogel crosslinked with calcium ions for the treatment of ovarian cancer was developed [ 66 ]. To form the cisplatin-loaded alginate nanogel, cisplatin (6 mg/mL) was mixed with an aqueous solution of alginate (2.0 mg/mL), heated at 95 °C, dialyzed and lyophilized.…”
Section: Alginate-based Hydrogels and Scaffolds For Cancer Treatmentmentioning
confidence: 99%
“…Moreover, it has the specific ability to form hydrogels with a high water content that makes them similar to native soft tissue. The alginate-based hybrid system of cisplatin-loaded alginate nanogel encapsulated in an injectable alginate hydrogel crosslinked with calcium ions for the treatment of ovarian cancer was developed [ 66 ]. To form the cisplatin-loaded alginate nanogel, cisplatin (6 mg/mL) was mixed with an aqueous solution of alginate (2.0 mg/mL), heated at 95 °C, dialyzed and lyophilized.…”
Section: Alginate-based Hydrogels and Scaffolds For Cancer Treatmentmentioning
confidence: 99%
“… Yamaguchi et al (2021) designed a cisplatin (CDDP)-loaded nanogel for peritoneally disseminated ovarian cancer to ensure adequate exposure of ovarian cancer cells to optimum concentrations of cisplatin. They developed “an alginate (AL)-based hybrid system in which a CDDP-loaded AL nanogel (AL/CDDP-nanogel) was encapsulated in an injectable AL-hydrogel cross-linked with calcium ions.” This matrix prevented the rapid clearance of CDDP and facilitated a sustained release of CDDP from the nanogel hybrid for over 1 week.…”
Section: Nanogels For Cancer Therapymentioning
confidence: 99%
“…An in vitro assay with a CD44 blocking/neutralizing antibody revealed that "hyaluronan receptor was involved in the nanogel internalization process." 2.5.9.4 Cisplatin-loaded nanogel for peritoneally disseminated ovarian cancer Yamaguchi et al (2021) designed a cisplatin (CDDP)-loaded nanogel for peritoneally disseminated ovarian cancer to ensure adequate exposure of ovarian cancer cells to optimum concentrations of cisplatin. They developed "an alginate (AL)based hybrid system in which a CDDP-loaded AL nanogel (AL/ CDDP-nanogel) was encapsulated in an injectable AL-hydrogel cross-linked with calcium ions."…”
Section: Nanogel Formulations For Ovarian Cancer Therapymentioning
confidence: 99%
“…Hydrogels are polymers with a three-dimensional network structure formed by covalent bonds, hydrogen bonds, van der Waals force, or ionic bonds. [1][2][3][4][5][6][7] With the advantages of adhesion, biocompatibility, and degradability, hydrogels are biomaterials with excellent performance and have important applications in tissue engineering, [8][9][10] wound dressing, [11][12][13][14] drug delivery, [15][16][17][18][19] and so on. Hydrogels can be divided into intelligent hydrogels and non-intelligent hydrogels.…”
Section: Introductionmentioning
confidence: 99%